Understanding Co‐Creation in a Research Partnership Programme Exploring Patient‐Driven Innovations: A Qualitative Longitudinal Study - Jansson, Hanna; Luckhaus, Jamie L.; Hasson, Henna; Mazzocato, Pamela; Stenfors, Terese; Wannheden, Carolina (Health expectations : an international journal of public participation in health care and health policy, 2024)
ABSTRACT Background Research indicates that successful co‐creation depends on a shared understanding of co‐creation and its related concepts. However, it also shows that, in practice, views on co‐creation and how to do it differ. This study aims to explore how patient innovators and researchers in a partnership research programme understand co‐creation and how this understanding changes over time. Methods An explorative longitudinal qualitative study was conducted with the ‘Patients in the Driver's Seat’ partnership research programme. Fifty‐eight interviews were performed and analysed using a reflexive thematic approach. Findings Four different ways of understanding co‐creation were identified. These can be instrumentally conceptualized as themes using the inputs‐process‐outputs model: (1) combining different perspectives, experiences and backgrounds (inputs); (2) deliberately dynamic and exploratory (process); (3) striving for equity, not equality (process); and (4) diverse value creation, tangible and intangible (outputs). Together, these themes represent the varied understandings of co‐creation among partnership programme members. Conclusions Our study of patient innovators and researchers identified four distinct yet complementary understandings of co‐creation. The study suggests that co‐creation is the sum of its essential components, which can be divided into inputs, process, and outputs. Patient or Public Contribution This study, and the partnership programme it explored, aims to improve the relevance of research for patients and informal caregivers through an improved understanding of the concept of co‐creation within research on patient innovation. All patient innovators involved in the programme were invited, as interviewees and researchers, to contribute to the study design and data analysis.